1982
DOI: 10.1002/art.1780250906
|View full text |Cite
|
Sign up to set email alerts
|

STRAIN and sex variation in the susceptibility to streptococcal CELL WALL–INDUCED POLYARTHRITIS IN THE RAT

Abstract: Sixteen inbred rat strains were examined for susceptibility and resistance to group A streptococcal cell wall-induced polyarthritis. The findings. indicated that 2 or more genetic loci, as well as sex-related factors, played a major role in determining susceptibility to arthritis in this model. Breeding studies demonstrated that susceptibility was a dominant or codominant trait. A positive association between the severity of arthritis and the development of chronic inflammation in multiple tissues was also obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
0
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 24 publications
9
104
0
1
Order By: Relevance
“…Briefly, a sterile aqueous suspension of sonicated SCW in phosphate buffered saline (PBS), pH 7.4, was injected intraperitoneally into female LEW/N rats at a dose equivalent to 20 pg of cell wall rhamnose per gm of body weight. This dose of SCW has previously been shown to induce severe chronic polyarthritis and granuloma formation with nearly 100% incidence in female LEW/N rats (14).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Briefly, a sterile aqueous suspension of sonicated SCW in phosphate buffered saline (PBS), pH 7.4, was injected intraperitoneally into female LEW/N rats at a dose equivalent to 20 pg of cell wall rhamnose per gm of body weight. This dose of SCW has previously been shown to induce severe chronic polyarthritis and granuloma formation with nearly 100% incidence in female LEW/N rats (14).…”
Section: Methodsmentioning
confidence: 96%
“…The preparation of peptidoglycan-polysaccharide fragments from group A streptococcal cell walls (SCW) and the induction of the polyarthritis were carried out as previously described in detail (14). Briefly, a sterile aqueous suspension of sonicated SCW in phosphate buffered saline (PBS), pH 7.4, was injected intraperitoneally into female LEW/N rats at a dose equivalent to 20 pg of cell wall rhamnose per gm of body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged neutrophil recruitment and activation can lead to tissue damage and eventually to inflammatory diseases (Feldmann et al, 1996;Barnes, 1998;Ajuebor et al, 2002). Many inflammatory diseases, such as rheumatoid arthritis and systemic lupus erythematosus, have a much greater incidence in women (Green, 1992;Da Silva, 1995;Gaillard et al, 1998;Castagnetta et al, 2002), and there is a similar sexual dimorphism in animal models of inflammatory disease (Wilder et al, 1982;Allen et al, 1983;Griffiths et al, 1994). We have shown that sex differences in the inflammatory response in rats are adrenal medulla dependent (Green et al, 1999), and that activation of the sympathoadrenal system by stress or noxious stimulation inhibits the inflammatory response (Green et al, 1997;Strausbaugh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that arthritis susceptibility in rats is strongly dependent upon strain and hormonally mediated sex linked effects (16,(17)(18)(19). For example, LEW/N female inbred rats develop severe polyarthritis with 100% incidence, whereas LEW/N males and F344/N males and females are relatively resistant.…”
mentioning
confidence: 99%